The Role of Digital Library Information Systems in Improving Collection Data Accuracy in Junior High Schools: A Qualitative Case Study Approach - Evi Sulistiyani; Andi Kristanto; Mohammad Syahidul Haq (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to explore the role of digital library information systems in improving the accuracy of collection data in junior high schools through a qualitative case study approach. Collection data accuracy is a crucial aspect of library management that directly impacts service quality and learning effectiveness. The research was conducted over six months (August 2024 - January 2025) at a junior high school that had implemented a digital library information system for at least two years. Research informants consisted of 3 librarians, the principal, vice principal for curriculum, 5 subject teachers, and 10 students selected purposively. Data were collected through participatory observation, in-depth interviews, focus group discussions, and document analysis, then analyzed using thematic analysis techniques with ATLAS.ti 9. Research findings show significant improvements in collection data accuracy after digital system implementation: bibliographic data accuracy increased from 68% to 94%, data duplication rates decreased from 23% to 3%, format inconsistencies reduced from 35% to 5%, and inventory time decreased from 14 days to 3 days. Automatic validation features detected 87% of data entry errors, while barcode and RFID technology improved the accuracy of circulation transaction recording to 98%. User satisfaction with collection information accuracy increased from 62% to 91%, with an 85% decrease in complaints. Findings indicate that implementation success was supported by librarian competence, school management support, continuous training programs, and an organizational culture that supports innovation. This research confirms the relevance of the DeLone & McLean Information Systems Success Model and Technology Acceptance Model in the Indonesian school library context, and provides practical implications for schools planning library digital transformation by emphasizing the importance of a holistic approach integrating technological aspects, human resources, and organizational support to realize effective and user-oriented library management.